Simulating Dynamic Time Dilation in Relativistic Virtual Environment - Abbas Saliimi, Lokman; Ngahzaifa, Ab. Ghani; Lok, Leh Leong (IACSIT Press, 2016)
This paper critically reviews several Special Relativity simulation applications and proposes a method to dynamically simulate Time Dilation effect. To the authors’ knowledge, this has not yet been studied by other researchers. Dynamic in the context of this paper is defined by the ability to persistently simulate Time Dilation effect based on specific parameter that can be controlled by user/viewer in real-time interactive simulation. Said parameter is the value of speed from acceleration and deceleration of moving observer. In relativistic environment, changing the speed’s value will also change the Lorentz Factor value thus directly affect the Time Dilation value. One can simply calculate the dilated time by using Time Dilation equation, however if the velocity is not constant (from implying Special Relativity), one must repeatedly calculate the dilated time considering the changing value of displacement/distance and time. This paper discusses the proposed method by dissecting Time Dilation equation and relates it to computational method available nowadays in order to dynamically calculate and ultimately simulate Time Dilation effect in relativistic virtual environment.